Assessment of Stress, Anxiety, and Depression in Oral Lichen Planus Patients: A Hospital-Based Study - Shalini Basu; Sunita Srivastava; Abhιshek Sinha; Haider Iqbal; Anuj Mishra; Yakshi Singh (Wolters Kluwer Medknow Publications, 2024)
Background: Oral lichen planus(OLP) lesions are chronic, rarely undergo spontaneous remission, potentially pre-malignant and often source of morbidity when erosive/ulcerative or erythematous lesions are present, suggesting that oral lichen planus does have an impact on quality life.It can be triggered by psychological or physical stress. Aim: was to determine the influence of stress anxiety and depression in patients with OLP using ,Depression ,stress and anxiety scale 21 questionnaire(DASS21). Methods: 90 patients were enrolled into this study. Psychometric evaluation was done using DASS-21 questionnaire. Patients were asked to rate the extent to which they had experienced each symptom over the previous week on a four-point scale ranging between 0 .Based on the score obtained, extent of a given negative emotion was classified as normal, mild, moderate, severe or extremely severe. It has 21questions divided into three sub scales of seven items each to evaluate the effect of stress, anxiety and depression respectively among OLP patients. Results: The atrophic-erosive type showed highest stress levels ie 16.7%,while,1.5% of the patients showed severe stress level in reticular type .(p-value of 0.005) whereas severe levels of anxiety was seen in 10.4% with reticular type, 8.3% with atrophic-erosive type and combined type with 9.1%. Extremely severe levels of anxiety was seen only in 3% of reticular type , 8.3% with atrophic-erosive pattern and 9.1% showed combined pattern. The results were not statistically significant. Conclusion: OLP have periods of relapses and remissions. burning sensation were high, irrespective of the clinical pattern seen. We found that the levels of stress and anxiety were comparatively higher compared to depression in patients with oral lichen planus.